2018
DOI: 10.1159/000489790
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transarterial Embolization/Chemoembolization-Based Locoregional Treatment with Sorafenib Prolongs the Survival in Patients with Advanced Hepatocellular Carcinoma and Preserved Liver Function: A Propensity Score Matching Study

Abstract: Background: Sorafenib is the standard treatment for patients with Barcelona Clinic Liver Cancer (BCLC) stage C hepatocellular carcinoma (HCC). However, the treatment outcome is not satisfactory. We retrospectively analyzed whether adding transarterial embolization/chemoembolization (TA(C)E)-based locoregional therapy to sorafenib can further improve treatment efficacy. Patients and Methods: We included 147 BCLC stage C HCC patients with Child-Turcotte-Pugh class A liver function and treated with sorafenib for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Our result, that the OS of patients with advanced HCC treated with combination therapy was superior to that of those patients treated with sorafenib alone, maps to the conclusions of 4 retrospective studies [19,31,56,57] but is in contrast to a clinical trial by Zhang and colleagues in 2015 [43]. In this study, despite a numerically greater median OS in the combined-therapy group than in the sorafenib-alone group (7.3 months vs. 6.0 months), no difference was observed between the two groups (P = 0.924).…”
Section: Discussionsupporting
confidence: 85%
“…Our result, that the OS of patients with advanced HCC treated with combination therapy was superior to that of those patients treated with sorafenib alone, maps to the conclusions of 4 retrospective studies [19,31,56,57] but is in contrast to a clinical trial by Zhang and colleagues in 2015 [43]. In this study, despite a numerically greater median OS in the combined-therapy group than in the sorafenib-alone group (7.3 months vs. 6.0 months), no difference was observed between the two groups (P = 0.924).…”
Section: Discussionsupporting
confidence: 85%
“…1). 15,16,22–28 Across the nine studies, there were a total of 3868 patients, of which 1181 patients were from the TACE plus sorafenib group and 2,687 patients were from the sorafenib group. The characteristics of each study are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Sorafenib is a multikinase inhibitor that could inhibit the proliferation of liver cancer cells. Its function of anti‐tumor angiogenesis could inhibit the synthesis of HIF‐1α protein and suppress the overexpression of VEGF induced by TACE 22,41,42 . As a tyrosine kinase inhibitor, sorafenib could also inhibit the receptors of VEGF and regulate the downstream cellular pathway 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of sorafenib combined with TACE in the treatment of advanced HCC were not satisfactory, the combination of apatinib with TACE may provide a new method of combination therapy. Several retrospective studies compared sorafenib combined with TACE versus sorafenib alone for advanced HCC and found that combination therapy improved the patients' survival [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent phase III clinical trial showed that the addition of TACE to sorafenib failed to achieve significant survival benefit [6]. The reported median OS in sorafenib plus TACE group ranged between 12.8 and 17.3 months [6,[14][15][16]. In contrast, although the combination of apatinib with TACE was compared with TACE alone, the median OS of the combined treatment group was reported to be 11.9-22 months [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%